Entrepreneurship in Post-conflict Transition: The Role of Informality and Access to Finance - Demirgüç-Kunt, Asli (2012)
We examine new self-employment entry and its viability in Bosnia and Herzegovina, using a rich household survey for the years 2001-2004. We find that wealthier households are more likely to engage in viable self-employment and create employment suggesting an important role for financing constraints. Specifically, although having an existing bank relationship is not significantly related to the entry decision, it is positively related to the survival for new entrepreneurs and their employment creation. We also find a non-linear relationship between remittances and entry in that individuals not receiving remittances are more likely to enter self-employment; but, if they do receive them, the likelihood of starting a business increases in the fraction of wealth received from domestic remittances. Finally, people working in the informal sector are more likely to become viable entrepreneurs, particularly those provided with loans from micro-credit organizations. These findings support the perception of the informal sector as an incubator for formal self-employment in the early years of transition.